2018
DOI: 10.3389/fmed.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Sympathetic Nervous System and Its Modulation in Renal Hypertension

Abstract: The kidneys are densely innervated with renal efferent and afferent nerves to communicate with the central nervous system. Innervation of major structural components of the kidneys, such as blood vessels, tubules, the pelvis, and glomeruli, forms a bidirectional neural network to relay sensory and sympathetic signals to and from the brain. Renal efferent nerves regulate renal blood flow, glomerular filtration rate, tubular reabsorption of sodium and water, as well as release of renin and prostaglandins, all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 69 publications
2
102
0
3
Order By: Relevance
“…The basal tachycardia presented by mice with periodontitis corroborates the hypothesis of sympathetic overactivation. It is well established that sustained sympathetic overactivity has been associated with the development of end-organ damage, such as cardiac hypertrophy and deterioration of kidney function 39 . In this context, the finds of the current study support the notion of increased cardiovascular risk associated with gingival infection in the model evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The basal tachycardia presented by mice with periodontitis corroborates the hypothesis of sympathetic overactivation. It is well established that sustained sympathetic overactivity has been associated with the development of end-organ damage, such as cardiac hypertrophy and deterioration of kidney function 39 . In this context, the finds of the current study support the notion of increased cardiovascular risk associated with gingival infection in the model evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of increased renal sympathetic nerve activity on renal perfusion and metabolism, which is acknowledged as a central actor in the pathogenesis of primary hypertension 29 and renovascular hypertension, 30 has been the subject of a large number of studies, and has been excellently reviewed in recent literature. 31,32 The innervation is predominantly adrenergic. Increased renal sympathetic nerve activity causes a reduction of the renal blood flow and GFR, and reduction of sodium and water excretion.…”
mentioning
confidence: 99%
“…NE released from the nerve terminals, together with co-transmitters, such as ATP and neuropeptide Y, regulate kidney function [35]. NE in the kidney is involved in a number of physiological processes, including control of renal blood flow, glomerular filtration rate, reabsorption of water, sodium, and other ions, and release of renin [6]. We recently found that renal nerve-derived NE signaling via α 2 -ARs, promotes renal inflammation and interstitial fibrosis [25,31].…”
Section: Adrenergic Receptors and Norepinephrine In The Kidneymentioning
confidence: 99%
“…The kidneys are abundantly innervated by both renal afferent sensory and efferent sympathetic nerves and communicate with the central nervous system via the sensory afferent nerves [6,7]. Increased renal afferent activity directly influences sympathetic outflow to the kidneys via efferent nerves [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation